GENDER, SECURITY, AND CLIMATE CHANGE NEXUS: TAKING VIOLENCE PREVENTION SERIOUSLY IN THE GLOBAL SOUTH - Hanifah, Laila, Ms (Global: Jurnal Politik Internasional, 2024)
According to prior studies, a significant proportion of individuals affected by conflict regularly demonstrate that women experience violence to a greater extent. As the Cold War era came to an end, trends in major armed conflicts began to shift. Climate change has emerged as a new non-traditional security threat around the world, similar to traditional security challenges. The UNFCC recognises that women are disproportionately vulnerable and bear a greater burden from the impacts of climate change. Yet despite this, women are often marginalised from discourses on security. Research on security, gender and climate change shows that the consequences of climate change, such as disasters, water scarcity and food insecurity, have a significant impact on conflict and violence, particularly increasing sexual and gender-based violence. Ultimately, this article shows that women's different experiences and knowledge are critical to consider in security projects in the global South to minimise conflict and build a global society that is resilient to climate change. Using literature review case studies in Haiti, South Sudan, Somalia, Zimbabwe and Indonesia, this article presents an overview of security projects in the South that aim to prevent violence. It also provides a balanced critique of existing efforts at the intersection of gender, security, and climate change.